Kejahatan Body Shaming di Indonesia dalam Perspektif Hukum Pidana Islam - Hakim, Fatimah Khairul; Suparmin, Sudirman (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This study aims to examine the crime of body shaming in Indonesia from the perspective of Islamic criminal law. This study uses a normative legal research method with a comparative approach. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that body shaming, both verbal and non-verbal, is a reprehensible act that contradicts human values and is strictly prohibited in Islam, as emphasized in Q.S. Al-Hujurat verse 11 which prohibits acts of ridicule, reproach, and calling others by bad nicknames, and emphasizes the importance of guarding one’s tongue and using excellent and constructive words. In the legal context, body shaming falls into the category of jarimah ta’zir in Islamic criminal law and can be prosecuted under articles related to insult and defamation in positive law in Indonesia. This study recommends various preventive efforts, such as comprehensive public campaigns and education programs about the dangers of body shaming and the importance of respecting physical diversity, including integrating these values into the education curriculum and strict law enforcement. Collaboration between the government, judges, religious leaders, educators, and the community is expected to create a more inclusive environment that values everyone regardless of physical appearance.